Pengaruh Literasi Digital terhadap Literasi Kesehatan Digital Tenaga Kesehatan di Indonesia - Destrity, Nia Ashton; Rakhmawati, Fariza Yuniar; Alfira, Nisa (Fakultas Ilmu Komunikasi UKWMS, 2025)
The advancement of information and communication technology requires healthcare professionals to have strong digital competencies in consuming, acting upon, and producing digital health information. In Indonesia, some social media content created by healthcare professionals has been deemed unethical or unwise, highlighting the importance of digital literacy in this sector. Although studies on digital literacy and digital health literacy exist, research specifically focusing on Indonesian healthcare professionals is still limited. This study aims to analyze the influence of digital literacy on digital health literacy among healthcare professionals. Using a survey method, an online questionnaire was distributed to 387 respondents. The findings indicate that respondents’ levels of digital literacy and digital health literacy are moderate. While respondents generally perceive themselves as proficient in technical digital skills, they report lower confidence in broader digital competencies such as sharing opinions, participating in online activities, and protecting themselves from internet-related risks. Although they demonstrate stronger operational skills, they encounter challenges in navigating digital health information, evaluating the reliability of information, safeguarding personal privacy, and adding self-generated content. These results confirm that digital literacy significantly influences digital health literacy, emphasizing the need for healthcare professionals to develop comprehensive digital skills. Strong digital capabilities are essential for engaging effectively with digital health information and establishing credibility as sources on social media. The study underscores the urgent need to enhance digital capacity, particularly in device security, information navigation, content creation, digital participation, and protection from privacy breaches and other online risks. ABSTRAK Perkembangan teknologi informasi dan komunikasi menuntut tenaga kesehatan untuk memiliki kompetensi digital dan keterampilan dalam mengonsumsi, mengambil tindakan atas, serta memproduksi informasi kesehatan digital. Beberapa tahun terakhir, terdapat sejumlah konten media sosial oleh tenaga kesehatan di Indonesia yang dinilai kurang etis dan bijak. Sejumlah studi mengenai literasi digital dan literasi kesehatan digital telah dilakukan. Namun, di Indonesia masih terbatas studi mengenai literasi digital dan literasi kesehatan digital tenaga kesehatan. Riset ini ditujukan untuk menguji dan menganalisis pengaruh literasi digital terhadap literasi kesehatan digital pada tenaga kesehatan. Metode survei dilakukan melalui kuesioner daring kepada 387 tenaga kesehatan. Hasil riset menunjukkan bahwa secara umum, literasi digital dan literasi kesehatan digital responden berada pada tingkat moderat. Responden cenderung menilai diri mereka lebih memiliki keterampilan teknis digital dibandingkan kompetensi digital yang mencakup berbagi opini, berpartisipasi, dan perlindungan dari risiko penggunaan internet. Responden lebih unggul dalam keterampilan operasional, namun menghadapi tantangan dalam menavigasi, mengevaluasi reliabilitas, melindungi privasi, dan menambahkan konten yang telah diproduksi sendiri. Temuan ini menegaskan bahwa literasi digital memiliki pengaruh signifikan terhadap literasi kesehatan digital, menunjukkan bahwa kemampuan digital yang baik menjadi elemen penting bagi tenaga kesehatan untuk mendukung keterlibatan mereka memanfaatkan internet dalam konteks kesehatan serta partisipasi aktif sebagai sumber informasi di media sosial. Studi ini memperkuat urgensi peningkatan kapasitas digital terutama terkait keamanan perangkat digital, navigasi dan produksi pesan, partisipasi dalam aktivitas digital, dan perlindungan privasi serta risiko lain dari penggunaan internet.